Discreteness of subgroups of $SL(2,\boldsymbol{C})$ containing elliptic elements - Tukia, Pekka; Wang, Xiantao (MATHEMATICA SCANDINAVICA, 2002)
The following result is the main result of the paper. Let $G\subset \boldsymbol{SL}(2,\boldsymbol C)$ be non-elementary. If $G$ contains an elliptic element of order at least 3, then $G$ is discrete if and only if each non-elementary subgroup generated by two elliptic elements of $G$ is discrete.